Antibacterial Activity of Cananga Extract (Cananga odorata (Lam.) Hook.F. & Thomson) Against Streptococcus Mutans and Pseudomonas Aeruginosa Bacteria - I Putu Gede Adi Purwa Hita; Putu Yudhistira Budhi Setiawan; Ni Putu Wintariani; Dewi anggarini (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Streptococcus mutans is a gram-positive bacterium commonly found in the oral cavity, while Pseudomonas aeruginosa is a gram-negative rod-shaped bacterium that can form biofilms. Objective: The objective of this study was to determine the antibacterial activity of 96% ethanol extract of ylang-ylang flowers (Cananga odorata (Lam.) Hook.f. & Thomson) against S. mutans and P. aeruginosa using the disk diffusion method. Methods: This was an experimental study with a post-test only control group design. Results: The test results showed that ylang-ylang flower extract exhibited antibacterial activity against S. mutans with an average zone at a 40% concentration of 16.6 ± 2.5 mm, categorized as strong. Meanwhile, against P. aeruginosa, the average inhibition zone at a 40% concentration was 7.2 ± 2.2 mm, categorized as moderate. Phytochemical analysis showed that kenanga flower extract contains flavonoids, saponins, tannins, steroids, monoterpenes, and alkaloids. Conclusion: 96% ethanol extract of kenanga flowers effectively inhibits the growth of S. mutans and P. aeruginosa at a concentration of 40%. These results indicate that kenanga has potential as a natural antibacterial source for development in the pharmaceutical field.